Delayed diagnosis of multiple systemic disseminated tuberculosis: A case report. Issue 7 (18th February 2022) - Li, Huan; He, Fang; Zhong, Cejun; Qu, Junyan
Abstract: Rationale: The clinical manifestations in patients with disseminated tuberculosis (TB) are nonspecific and may present challenges for early diagnosis. Patient concerns and diagnoses: We describe the case of a 44-year-old man who presented with abdominal pain and discomfort for more than a month. He had undergone surgery for a chest wall abscess 9 months ago. Computed tomography scans showed a miliary pattern in the lung and multiple abscesses in the liver, spleen, left psoas major muscle, skin, and soft tissue, with rim enhancement. Mycobacterium tuberculosis was detected in the drainage fluid of the abscesses and surgical slices, and disseminated TB was diagnosed. Interventions and outcomes: With anti-tuberculosis therapy, the abscesses were gradually absorbed and all cultures were negative. Lessons: The patient exemplifies the difficulty of the early diagnosis of disseminated TB. Disseminated TB should be considered first in patients with multisystem illness, and then evidence should be pursued relentlessly to establish a diagnosis.